THE SIZE AND POSITIONAL RELATIONSHIP OF THE MEDIAL PATELLOFEMORAL LIGAMENT IN EARLY PEDIATRIC DEVELOPMENT. Issue 3 (31st March 2019) - Wilson, Philip L.; Ellis, Henry B.; Green, Daniel W.; Tompkins, Marc; Dingel, Aleksei; Ganley, Theodore J.; Fabricant, Peter D.; Yen, Yi-Meng; Stavinoha, Tyler J.; Shea, Kevin
Background: Knowledge of the medial patellofemoral ligament (MPFL) size and positional relationship to the articular cartilage is not well understood in pediatrics. The purpose of this study was to analyze the size and position of the MPFL relative to the articular surface of the pediatric patella. Methods: 39 pediatric cadaveric knee specimens (age range 1 month-11 years, 24 male) were dissected by fellowship-trained, pediatric orthopedic surgeons to expose the MPFL insertion to the patella (Figure 1A). Digital calipers (Mahr, MarCal 16EWRi) were used to record the proximal to distal cartilaginous articular surface length and the proximal to distal extent (zone) of MPFL patellar insertion. The ratio of the patellar articular cartilage length covered by the zone of MPFL patellar insertion was calculated. The center-point of the zone of MPFL patellar insertion was also recorded as a percentile distance from the superior margin of the articular cartilage of the patella. These measures were analyzed by age and Spearman's Correlation coefficients were calculated. Results: Both patellar articular cartilage length (p<0.001, rs 0.803) and zone of MPFL patellar insertion (p<0.001, rs 0.691) increased with age. The zone of MPFL patellar insertion averaged 8.34 mm in specimens <6 mos.; 11.73 mm in specimens ages 1-4 years; and 16.03 mm in specimens ages 5-11 years. The ratio of the patellar articular cartilage length covered by the zone of MPFL patellar insertion had a significant reduction with age (p=0.001, rs -0.499); decreasing from 66% and 55% in the two younger age groups, to 45% of the cartilage length with MPFL patellar insertion coverage in the school-age 5-11 year-old specimens. The center-point of the MPFL patellar insertion increased in distance from the superior pole of the articular cartilage of the patella with age (p< 0 .05, rs 0.397); starting slightly above (39% and 46%) and assuming a mid-pole (49%) position along the articular cartilage length in the school-age 5-11 year-old specimens (Figure 1B). Conclusion: In pre-ambulatory and early childhood years, the MPFL inserts on a large portion of the medial border of the patella, covering a distance >50% of the articular surface length and centered above the mid-point of the articular cartilage. During maturation, the length of the articular cartilage of the patella increases at a rate greater than the MPFL, resulting in an MPFL insertion averaging 45% the length of the articular surface and centered near the center-point of the articular cartilage (mean = 49th percentile from the superior border) in school age, pre-adolescents. Significance: Knowledge of the MPFL position relative to the articular cartilage length in children may add to understanding of the development of patellar instability, and aid in the accurate reconstruction of the ligament during treatment. Fig. 1A: Photograph of Medial Patellofemoral Ligament dissection in a 5-year-old specimen Fig. 1B: Relationship of the Pediatric Medial Patellofemoral Ligament to the Patellar Articular Cartilage